An option pricing approach to the estimation of downside risk: a European cross-country study - Alles, Lakshman (Palgrave Macmillan Ltd, 2008)
The purpose of this paper is to undertake a comparative study of the costs of downside protection for investors in the four major European stock markets: UK, Germany, France and Italy, and to investigate the time diversification effects in these markets by examining the variation of this cost as the investment horizon is extended. The cost of downside protection and time diversification effects are investigated by examining the properties of a protective put strategy and a capital protected equity participation strategy in each country’s stock market over investment horizons ranging from 1 to 20 years. Long-horizon investment outcomes are generated using a bootstrapping technique. Results indicate that the cost of downside protection differs from one country to another, but there is a common pattern of the cost decreasing as the investment horizon lengthens. In overall terms, the pattern of decreasing protection costs at longer investment horizons is consistent with the notion of the time diversification benefits of investment risk.